Corruption: A Malaise in Need of a Remedy - Arambam Sophia, (Technium Social Sciences Journal, 2020)
The World Bank (1997) defines corruption as “Abuse of public power for private gain”. Corruption is a complex phenomenon with its roots lying deep in bureaucratic and political institutions. Though it is an issue of governance, there are deeper- seated factors too and complex causes and the means to control it are not fully understood. It thrives best in countries where there is poor design of economic policies, underdeveloped civil societies, low economic development and weak accountability of public institutions; conditions which are mainly prevalent in less developed countries. Though systemic corruption may co-exist with strong economic performance, experience across the world suggests that corruption is not conducive to development and might result in inefficiency in resource allocation. In underdeveloped economies like Manipur, it can spawn discontent and spew distrust in the system and becomes the breeding ground of separatist, revolutionary and other movements, which moves in a parallel path with the corrupt system and though it may mean much in terms of values and philosophy; in practice, it may further destabilise the system and derail the track to development. This paper is based only on secondary data sources and tries to understand the concept of corruption, its causes and consequences, especially with reference to an underdeveloped state like Manipur. It relies on secondary sources of data from government reports and publications, books, journals and other online articles etc.